Gene fitness landscapes of Vibrio cholerae at important stages of its life cycle. - Heather D Kamp; Bharathi Patimalla-Dipali; David W Lazinski; Faith Wallace-Gadsden; Andrew Camilli (PLoS Pathogens)
Vibrio cholerae has evolved to adeptly transition between the human small intestine and aquatic environments, leading to water-borne spread and transmission of the lethal diarrheal disease cholera. Using a host model that mimics the pathology of human cholera, we applied high density transposon mutagenesis combined with massively parallel sequencing (Tn-seq) to determine the fitness contribution of >90% of all non-essential genes of V. cholerae both during host infection and dissemination. Targeted mutagenesis and validation of 35 genes confirmed our results for the selective conditions with a total false positive rate of 4%. We identified 165 genes never before implicated for roles in dissemination that reside within pathways controlling many metabolic, catabolic and protective processes, from which a central role for glycogen metabolism was revealed. We additionally identified 76 new pathogenicity factors and 414 putatively essential genes for V. cholerae growth. Our results provide a comprehensive framework for understanding the biology of V. cholerae as it colonizes the small intestine, elicits profuse secretory diarrhea, and disseminates into the aquatic environment.